2006
DOI: 10.1074/jbc.m513772200
|View full text |Cite
|
Sign up to set email alerts
|

The Group B Streptococcal Sialic Acid O-Acetyltransferase Is Encoded by neuD, a Conserved Component of Bacterial Sialic Acid Biosynthetic Gene Clusters

Abstract: Nearly two dozen microbial pathogens have surface polysaccharides or lipo-oligosaccharides that contain sialic acid (Sia), and several Sia-dependent virulence mechanisms are known to enhance bacterial survival or result in host tissue injury. Some pathogens are also known to O-acetylate their Sias, although the role of this modification in pathogenesis remains unclear. We report that neuD, a gene located within the Group B Streptococcus (GBS) Sia biosynthetic gene cluster, encodes a Sia O-acetyltransferase tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 50 publications
5
92
3
Order By: Relevance
“…This behavior has also been noted for Sias released from the GBS surface by mild acid hydrolysis (17,18). of O-acetyltransferase-and O-acetylesterase-encoding genes (18,38), which may themselves produce enzymes with varied mechanisms and/or activity levels (Fig. 4) (51).…”
Section: New Understanding Enriches Model Of Gbs Sia O-acetylation-mentioning
confidence: 98%
See 3 more Smart Citations
“…This behavior has also been noted for Sias released from the GBS surface by mild acid hydrolysis (17,18). of O-acetyltransferase-and O-acetylesterase-encoding genes (18,38), which may themselves produce enzymes with varied mechanisms and/or activity levels (Fig. 4) (51).…”
Section: New Understanding Enriches Model Of Gbs Sia O-acetylation-mentioning
confidence: 98%
“…A polymorphism within the GBS O-acetyltransferase encoded by neuD is at least partially responsible for controlling the degree of O-acetylation in GBS, where 88C corresponds to the "low-O-Ac" phenotype (Ͻ5% O-Ac) and 88F corresponds to the "high-O-Ac" phenotype (Ͼ30% Sia-O-Ac) (18). Here we show that in high O-Ac GBS strains, NeuA prevents even greater levels O-acetylation (Ͼ70%) as observed in the NeuA esterase-inactive mutant (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only Grampositive bacterium reported to produce a sialic acidcontaining capsule is S. agalactiae, which possesses a sialyltransferase (CpsK) that adds a terminal a-2,3-linked Neu5Ac to galactose within the capsule's oligosaccharide repeat (Chaffin et al, 2005). Again, recent work has shown that this Neu5Ac residue can be modified by O-acetylation (Lewis et al, 2006).…”
Section: Deploying Sialic Acid Onto the Battlefieldsynthesis Of Sialimentioning
confidence: 99%